KAJIAN PELESTARIAN KAUMAN SEMARANG SEBAGAI KAWASAN WISATA RELIGI - Laila Nur Tsani; Rina Kurniati (Diponegoro University, 2019)
Preservation of the area is an effort to protect and maintain the authenticity and historical value in an area dynamically, which is carried out not only to get the purpose of building maintenance but functionally can generate revenue and profits for the region. Based on the RTRW Kota Semarang 2011-2031, Kauman is one of the cultural heritage areas. There are two types of historical heritage buildings in the Kauman area, Masjid Agung Semarang and several ancient houses which have Arabic architecture. Some old buildings were not maintained and neglected and have not received the attention of the government so that many experienced changes in the form and style of architectural buildings. Moreover, Kauman, which is known as a village with a high religious nuance, fades its values, character, and culture as the times progress. Therefore the purpose of this study is to study the preservation of Kauman Semarang as a religious tourism area. The research method in this study uses qualitative descriptive analysis with data collection techniques in the form of interviews and observations. The results of this study are preservation that is supported by the development of religious tourism in Kauman. The development is carried out on facilities and infrastructure for tourism support and tourism potential in Kauman in the form of culinary tours and religious education from Islamic boarding schools.